Budgeting in Municipalities - Astrauskas, Algirdas (Ekonomika, 1999)
The article aims, on the basis of theoretical knowledge and accumulated information from the individual Lithuanian municipalities, to analyse the currently existing legislation and the actual situation in applying the principles and methods of municipal budget formation. It is, inter alia, designed to identify the major problems in this sector and, drawing on the useful experience of other countries, to offer solutions to these problems.The author of the article has drawn the following conclusions:1. The legislation regulating municipal budget formation, administration, accounting and its supervision is outdated and therefore requires an accelerated change taking into account the useful experience of other states, as well as the specifics of Lithuania.2. Public institutions responsible for the management of methodological issues of municipal budget formation fail to prepare in due time new normative acts, do not take a profound approach to the solution of existing problems and are not willing to contract the most-advanced experts and employ their expertise.3. The normative acts of Lithuania do not provide for the principles of municipal budget formation, which are well established in the finance theory. Some of the principles, however, are implemented, as other laws have binding, although indirectly, provisions on municipalities in this respect. On the other hand, most of the principles, even after legitimising them, could not be put into practice because of the currently existing relations between public authorities and municipal institutions, and the limited rights and possibilities of municipalities to increase their revenue.4. Financial resources and funds of municipalities which are necessary to carry out the functions prescribed to them by law are not balanced out, i.e. the actual rather than the formal principle of budget balance is violated.5. The level of estimated municipal budget revenue is determined by public institutions rather than municipalities themselves; the rights of municipalities to fix the tax derived revenues tariffs and local fees independently are minimal; greater autonomy is granted to municipalities in planning non-tax derived revenues and the potential in this field has not yet been fully exhausted.6. The municipal system provides for minimum conditions which allow the interested and active members of the community to participate in the drafting of the budget; as a rule, observations and proposals from the residents are desirable, yet, the majority of municipalities tend to publish the approved budget rather than a draft budget before it is approved and do not seem to search for more attractive ways ensuring a more lively interest and broader participation of the public in the budget drafting process; instead, most primitive forms are employed.7. Lithuania’s legislation does not provide for the methods of municipal budget formation and their application. Therefore, municipalities, being short of both the necessary expertise and recommendations, draft budgets at their own discretion.8. The decision to give priority to a programme-based budget formation principle and implement it in the municipal system as of 2000, has raised serious doubts because of the shortage of professional proficiency of the personnel, lack of methods, high expenditure relating to the implementation of this method and the absence of well-functioning system of strategic management, which has not yet been developed.The solutions to the problems involve:1. The most expeditious change of legislation, which does not provide so far for municipal budget formation, implementation, accounting and supervision, to meet the present-day requirements and to be consistent with other legal acts. The best solution would be to draft and pass a special law on municipal budget, which would specify the sources of municipal revenues, the procedure for general and earmarked subsidising, set the mechanism for balancing out the financial capacities and required expenditures, establish the life cycle of the budget as well as the methods of budget formation etc.2. Drafting and adopting legal acts which would allow the municipalities to establish tariffs for local fees and fix local charges, provide for conditions and interest in increased municipal revenues and a more fair and transparent allocation of subsidies. It would enhance the municipal financial capacity, help to balance out municipal budgetary revenues and expenditures required to carry out the functions prescribed by law, i.e. to put into practice the principle of balanced budget - the most important principle today.3. Transition period is required for gradual implementation of the method of programme-based municipal budget formation, along with detailed and clearcut recommendations and measures for applying this method as well as prior training of municipal politicians and experts.Critical assessment of other methods of municipal budget formation and the possibilities of their application could lead to the selection of the most suitable ones and, in cases where the advantage of their application is evident, to their statutory provision.1. Lithuanian Municipalities’ Association could take up a responsibility of regularly summarising and spreading the best practice of the Lithuanian and other countries’ municipalities on:• the planning of long-tenn investments; establishing the procedure for drafting, consideration and approval of a budget; assessment of results of financial audit performed at municipalities;• the most justifiable ways for debating the draft budget in public.